2023
DOI: 10.1126/sciadv.ade7280
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase and reduced arterial tone contribute to arteriovenous malformation

Abstract: Mechanisms underlying arteriovenous malformations (AVMs) are poorly understood. Using mice with endothelial cell (EC) expression of constitutively active Notch4 (Notch4* EC ), we show decreased arteriolar tone in vivo during brain AVM initiation. Reduced vascular tone is a primary effect of Notch4* EC , as isolated pial arteries from asymptomatic mice exhibited reduced pressure-induced arterial tone ex vivo. The nitric oxide (NO) synthase (NOS) inhibitor NG-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…However, studies of these changes pathogenesis are multidirectional, which does not provide a holistic picture and requires further research on this issue. A well-known factor in the regulation of cerebral blood vessels is eNOS, the increase or decrease of which lead to vascular tone and permeability changes [10]. Lots of studies on eNOS in cerebrovascular disorders have shown that eNOS deficiency leads to dysregulation of systemic blood pressure and a decrease of the blood-brain barrier protective function [6,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of these changes pathogenesis are multidirectional, which does not provide a holistic picture and requires further research on this issue. A well-known factor in the regulation of cerebral blood vessels is eNOS, the increase or decrease of which lead to vascular tone and permeability changes [10]. Lots of studies on eNOS in cerebrovascular disorders have shown that eNOS deficiency leads to dysregulation of systemic blood pressure and a decrease of the blood-brain barrier protective function [6,25].…”
Section: Introductionmentioning
confidence: 99%